Amino acid-driven hydrophobization of alumina and production of particle stabilised foams in a broader pH range. Issue 12 (September 2020) - dos Santos, T.; Pereira, C.I.; Gonçalves, R.; Fernandes, C.H.M.; Salvini, V.R.; Pandolfelli, V.C.
Abstract: The interaction of amino acids (glycine, L-valine, L-isoleucine and L-leucine) with alumina surface was studied to induce partial hydrophobization and production of ultrastable particle-stabilised foams. The evaluation of these amino acids was carried out by mechano-quantum simulations followed by experimental tests (foamability, zeta potential, contact angle and foam lifetime measurements). The experimental results agreed with the trends pointed out by the simulations. The selected amino acids interact with alumina particles in aqueous media and in a broader pH range, leading to hydrophobization of surfaces, which was more intense for amino acids with higher molecular mass (isoleucine and leucine). As a consequence, ultrastable foams with a longer lifetime (> 100 h) were produced and the foam microstructure was preserved from ageing phenomena. Moreover, the attained foams were stable at different pH, opening up new possibilities to develop macroporous multiphasic ceramics, which can result in novel materials for thermal insulation at high temperatures.